Risk Factors of Difficult Intubation in Patients with Severe Obesity Undergoing Bariatric Surgery: A Retrospective Cohort Study - Ayten Saracoglu (8075222) (2025)
Background Obesity poses significant challenges by altering upper airway anatomy and making mask ventilation and tracheal intubation difficult. In 2023, 46.1% women and 35.9% men > 18 years were classified as obese in Qatar, yet intubation complications in this group have not been extensively studied. The aim of this study was to evaluate the frequency and types of intubation complications in adults with severe obesity undergoing bariatric surgery and to identify incidence of difficult intubation and associated risk factors. Methods In this retrospective cohort study, 2421 patients (1664 females and 746 males) were analyzed. All patients with severe obesity aged over 18 years with a BMI of 40 kg/m2 or higher, who underwent bariatric surgery from January 2014 to January 2024, were included. Difficult intubation was defined as the need for video laryngoscopy, cricothyrotomy, intubation via a supraglottic airway device, use of a stylet or bougie, more than one intubation attempt, or desaturation during intubation. Results None of the patients experienced any complications of interest. Video laryngoscope was used in 85 patients (3.5%), first-attempt intubation success rate was 95.4%, with more than one attempt required in 4.6% of cases. Logistic regression revealed that the odds of complicated intubation were 1.5 times higher in patients with a BMI > 60, 8.9 times higher in those with Cormack-Lehane class IV, and 5.1 times higher in patients with Mallampati score of IV. Comorbidities increased the odds by 1.3 times, with asthmatic patients having 2.1-fold higher odds. Conclusion This study highlights the challenges of tracheal intubation in patients with severe obesity undergoing bariatric surgery and the need for tailored strategies to manage these difficulties. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11695-025-07763-2